Dinâmica espaço-temporal da pesca industrial de camarão-rosa Farfantepenaeus subtilis na plataforma continental do Amazonas - MARTINS, Déborah Elena Galvão (Universidade Federal do Pará, 2013)
Knowledge of spatial distribution of fishing resources is essential to fisheries management. The southern brown shrimp Farfantepenaeus subtilis (Perez-Farfante, 1967) is an industrial fishing fleet target on the Amazon Continental Shelf. This study aimed to evaluate F. subtilis relative abundance spatial-temporal patterns from commercial fishery data, using Geographic Information System tools. Catch per unit effort (CPUE), used as index of relative abundance, was related to bathymetry, substrate characteristics, Amazon river flow and the oceanographic variables obtained by remote sensing: sea surface temperature and chlorophyll-a concentration. Analyzing substrate characteristics, the commercial shrimp trawls were concentrated at the mottled mud region, where the overlap of environmental factors was crucial for a higher incidence of F. subtilis. In this region, features such as substrate (mud), sedimentation rate (<1 cm.yr-1) and salinity (> 30) are the ideal habitat for F. subtilis. Higher CPUE values were associated with lower temperatures and higher values of chlorophyll-a concentration, which occur at the greatest flow of the Amazon river, during the first six months of the year. It was observed the occurrence of three periods with different levels of production along the year: from February to April, with higher CPUE of southern brown shrimp, from May to July, and August to September, with lower CPUE. The results showed that relative abundance of F. subtilis is not distributed uniformly in space nor in seasonal variation.